Computational validation of magnetorheological elastomers for engine mount application - Ladipo, Ismail; Ridhuan Siradj, Fadly Jashi Darsivan; Waleed, Fekry Faris (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Magnetorheological Elastomers (MREs) are a class of smart materials whose potentials in engineering applications have been attracting attention in the last few decades. In this study, a rheological model for MRE and its dynamic characterization as engine mounts is presented. The use of magnetic field in controlling the dynamic stiffness and damping modulus of the engine mounts in a quarter car model is simulated. The vibration level of the MRE engine mount is compared with Passive rubber mounts. The results show an improved performance with a reduction in relative displacement in the low frequency range. Sensitivity analysis technique is used to compare the MRE mount parameters to improve its performance. The adaptive MRE mounts could be extended to other applications in which vibration isolation is required.